2018
DOI: 10.2147/ott.s164503
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tubeimoside-1 on the proliferation, metastasis and apoptosis of oral squamous cell carcinoma in vitro

Abstract: BackgroundTubeimoside-1 (TBMS1), a triterpenoid saponin extracted from traditional Chinese medicine tubeimoside, exerts a cytotoxic effect on several human cancer cell lines. However, no study has focused on whether TBMS1 works on oral squamous cell carcinoma (OSCC).Materials and methodsWe treated OSCC cells with TBMS1 to detect the effect and relevant molecular basis of TBMS1 for the first time. We chose two oral cancer cell lines, CAL27 and SCC15, for this study. First, the 3-(4,5-dimethylthiazol-2-yl)-2,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Evidence from Yang et al [24] discovered that Icaritin could repress the progression of OSCC through hindering STAT3 signalling. In addition, Tubeimoside-1 (TBMS1) has been certified to refrain OSCC cell proliferation, migration and to accelerate apoptosis in vitro [25]. These findings seem to hint that TCMs are an effective agent for OSCC treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence from Yang et al [24] discovered that Icaritin could repress the progression of OSCC through hindering STAT3 signalling. In addition, Tubeimoside-1 (TBMS1) has been certified to refrain OSCC cell proliferation, migration and to accelerate apoptosis in vitro [25]. These findings seem to hint that TCMs are an effective agent for OSCC treatment.…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9] Tubeimoside-1 (TBMS1) is the main active ingredient of Rhizoma bolbostemmae, and studies have demonstrated that it suppresses proliferation and induces apoptosis of cells in cancers such as glioma, 10 glioblastoma, 11 non-small-cell lung cancer, 12 and oral squamous cell carcinoma. 13 TBMS1 is conventionally used to treat snake venoms and inflammation, and was included in Supplements to Compendium of Materia Medica published in 1765. 14 Furthermore, in acute lung-injured mice, TBMS1 could alleviate inflammation in lipopolysaccharide-induced RAW 264.7 cells.…”
mentioning
confidence: 99%
“…The highest-acquired active monomer TBMS1 which extracted from the tubers of Rhizoma Bolbostemmatis has proven its potential ability in the treatment of gastric cancer, liver cancer, cervical cancer, lung cancer, ovarian cancer, glioblastoma, esophageal cancer, etc [5,6,7,8,9,10]. At present, the anti-tumor mechanism of TBMS1 has been found to induce anti-tumor effects by inducing apoptosis [11,12], autophagy [13], cell cycle arrest [14,15], inhibition of cancer cell growth, metastasis [16], differentiation [17], angiogenesis [18] and inflammation [19]. Although the relevant critical pathways and molecular targets of TBMS1 have been confirmed, we need to further improve and explore the relevant mechanisms for the possible therapeutic application to the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%